SURVEY ON THE STATUS OF HEART FAILURE TREATMENT ACCORDING TO THE MINISTRY OF HEALTH GUIDELINES (2022) AT TRUNG VUONG HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the adherence to heart failure treatment guidelines issued by the Ministry of Health at Trung Vuong Hospital.Methods: A cross-sectional descriptive study was conducted on 119 heart failure patients. Logistic and linear regression analyses were utilized to identify factors influencing reduced ejection fraction and the total number of medication classes prescribed.Results: The proportion of patients receiving foundational medication classes was very high: renin-angiotensin system inhibitors (92.4%), sodium-glucose cotransporter-2 inhibitors (90.8%), mineralocorticoid receptor antagonists (84.8%), and beta-blockers (82.4%). Notably, 61.3% of patients achieved the standard quadruple therapy. Sodium-glucose cotransporter-2 inhibitors reached an optimal target dose rate of 89.9%. In contrast, renin-angiotensin system inhibitors, beta-blockers, and mineralocorticoid receptor antagonists had target dose achievement rates of less than 1%. Chronic kidney disease was the only statistically significant barrier that reduced the number of combined medication classes (regression coefficient B = -0.670; p < 0.001).Conclusion: Trưng Vương Hospital has successfully implemented early multidrug therapy for heart failure patients, particularly with the prominent use of sodium-glucose cotransporter-2 inhibitors. However, the target dose achievement rate for conventional medications remains low, necessitating individualized dose titration strategies.
Keywords: Heart failure, ejection fraction, renin-angiotensin system inhibitors, beta-blockers, mineralocorticoid receptor antagonists.